Towards culturally sensitive tourism: the educational role of the Sámi tourism guidelines - Doriana Plesa (Matkailututkimus, 2024)
The tourism industry’s growth has resulted in unethical impacts on the local communities which prompted the implementation of controls such as policies, codes of conduct, and indigenous tourism guidelines to maintain ethical standards. While policies and codes have been widely studied, research on indigenous tourism guidelines is limited. The master’s thesis, which this text is based on, aimed to understand how the principles for responsible and ethically sustainable Sámi tourism are recognized and implemented and to explore their role in enhancing cultural sensitivity. The conceptual framework was guided by Viken et al.’s (2021) study on cultural sensitivity, which considers sensitive behaviors as guided by respect, recognition, and reciprocity. The main findings suggested that tourism actors in Finnish Sápmi actively engage in promoting cultural sensitivity towards the Sámi people and show awareness and implementation of the Sámi tourism guidelines. Additionally, cultural education was identified as an opportunity to enhance cultural sensitivity. Indeed, the study participants emphasized the educational role that the Sámi tourism guidelines have played in their work since implementation.